Dampak Perkembangan Media Digital terhadap Karakter Generasi Remaja Menurut Pandangan Islam - Muhammad Royan Alfattih; Rasyad Burhanudin Subagio (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of digital media has fundamentally transformed the social landscape in which adolescents grow up, raising serious concerns about its impact on character formation. Adolescence is a pivotal phase of identity development, moral reasoning, and value internalization. However, the unrestricted penetration of digital content from social media platforms to streaming services has been shown to erode religious values, weaken social bonds, and encourage hedonistic behavior among youth. This study aims to analyze the impacts of digital media development on the character of adolescents from an Islamic perspective, using a qualitative library research (studi pustaka) method. Data were gathered from scientific journals, Islamic primary sources (the Qur'an and Hadith), and contemporary research publications from 2015 to 2025. The findings indicate that digital media carries a dual nature: it can be a powerful tool for Islamic education and moral reinforcement, yet simultaneously poses grave threats to adolescent spirituality, social behavior, and intellectual integrity. The study recommends that Islamic education institutions, families, and policymakers work collaboratively to build a framework of digital akhlak grounded in Maqashid al-Shariah principles protecting religion (hifdz al-din), life (hifdz al-nafs), intellect (hifdz al-'aql), lineage (hifdz al-nasl), and property (hifdz al-mal) as a guiding ethical compass for adolescents navigating the digital age.